NUTCRACKER SYNDROME IN CHILDREN: A SINGLE CENTRE EXPERIENCE - Ratković-Janković, Marija (Acta medicae Medianae, 2024)
Nutcracker syndrome (NS) is a rare cause of hematuria and/or proteinuria defined as the left renal vein entrapment between the abdominal aorta and the superior mesenteric artery. The majority of patients, mostly females, are diagnosed in puberty age. We report eight children diagnosed with NS analyzing their clinical features, diagnostics approaches, disease evolution and treatment outcomes.